Symptom reduction and termination: client change and therapist identified reasons for saying goodbye. Issue 1 (2nd January 2019) - Bartholomew, Theodore T.; Lockard, Allison J.; Folger, Susan F.; Low, Blakely E.; Poet, Andrea D.; Scofield, Brett E.; Locke, Benjamin D.
Abstract: Empirical efforts have focused on predicting whether or not clients prematurely terminate therapy, with nonattendance of last session equated to premature termination. However, this fails to explore the relationship between clients' distress reduction and reasons for termination. With this study, we aimed to understand how clients' distress change relates to premature termination and examine clients' distress change in conjunction with therapists' perceptions of termination reasons. We collected data from 797 clients who prematurely terminated or attended termination but completed therapy a minimum of three individual sessions provided by 38 therapists. Clients completed an assessment of psychological symptoms before each session. At the end of treatment, therapists identified the reasons they believed termination occurred for all clients in the sample. Results demonstrate that total sessions attended and missed predict premature termination, whereas distress change does not. Additionally, clients who were believed to accomplish goals do show greater change. However, therapists' indicated that over half of clients did not reach goals at termination and they did not perceive nonattendance at last session to equate to drop out in all cases. Implications are discussed with respect to understanding why clients' terminate, therapeutic goal conceptualization, and review of goals during termination in time-limited psychotherapy.